STING pathway contributes to Steroid-Hyporesponsive Lung Inflammation in DSS-induced colitis mice model - Mariam Wed Eladham; Narjes Saheb Sharif-Askari; Bushra Mdkhana; Shirin Ali; Baraa Khalid Salah Al-Sheakly; Nival Ali; Balachandar Selvakumar; Fatemeh Saheb Sharif-Askari; Ibrahim Hachim; Rabih Halwani (PLoS ONE, 2026)
Background Inflammatory bowel disease (IBD), a chronic inflammation of the gastrointestinal tract, is well recognized for triggering extraintestinal manifestations, including pulmonary complications. Emerging evidence highlights the gut lung axis (GLA) as a critical link in respiratory health, where gut dysbiosis and bacterial translocation play a role in systemic and pulmonary inflammation. Despite its clinical relevance, the mechanisms underlying these pulmonary manifestations remain poorly understood. The Stimulator of Interferon Genes (STING) pathway plays a critical role in regulating pulmonary inflammation. However, its precise role in colitis-associated lung inflammation remains unclear and could provide novel insights into the pathogenesis of this condition. Methods This study evaluates the involvement of STING pathway in colitis induced lung tissue inflammation using a dextran sulfate sodium (DSS) murine model of colitis. The effect of STING inhibitor on regulating steroid hypo-responsiveness, particularly the glucocorticoid receptor GR-α/GR-β ratio, is also examined. Results The DSS model induces lung inflammation, characterized by enhanced infiltration of inflammatory cells into lung tissues, increased levels of IL-17, IFN-γ, bacterial DNA, while enhancing steroid hypo-responsiveness. The inhibition of STING controls lung inflammation and restores steroid sensitivity to a much higher extent compared to dexamethasone treatment. Conclusion The significant activation of the STING pathway and dysregulation of steroid signature markers in the lungs of DSS-induced colitis mice suggest a novel mechanism by which gut inflammation may propagate to the lungs.